Cost-Effectiveness of Anti-Epidermal Growth Factor Receptor Therapy Versus Bevacizumab in KRAS Wild-Type (WT), Pan-RAS WT, and Pan-RAS WT Left-Sided Metastatic Colorectal Cancer - Lee, Shing Fung; Choi, Horace C. W.; Chan, Sik Kwan; Lam, Ka On; Lee, Victor H. F.; Wong, Irene O. L.; Chiang, Chi Leung (Frontiers in Oncology, 2021)
Objectives: We aimed to compare the economic value of chemotherapy plus anti-epidermal growth factor receptor (EGFR) therapy against chemotherapy with bevacizumab (Bev, an anti-vascular endothelial growth factor therapy) in KRAS wild-type (WT), pan-RAS WT and pan-RAS WT left-sided metastatic colorectal cancer (mCRC) patients from the Hong Kong societal perspective. Materials and Methods: We developed Markov models and 10-year horizon to estimate costs, quality-adjusted life years (QALYs), and incremental cost-effectiveness ratio (ICER) of chemotherapy plus anti-EGFR therapy against chemotherapy plus Bev in KRAS WT, pan-RAS WT, and pan-RAS WT left-sided mCRC. We considered two times of the local gross domestic product per capita (GDPpc) as the willingness-to-pay (WTP) threshold (2x GDPpc; US$97,832). Results: Adding anti-EGFR mAb to chemotherapy provides additional 0.24 (95% confidence interval [CI] 0.19–0.29), 0.32 (95% CI 0.27–0.37), and 0.57 (95% CI 0.49–0.63) QALY compared to adding Bev in KRAS WT, pan-RAS WT, and left-sided pan-RAS WT mCRC populations respectively. The corresponding ICER is US$106,847 (95% CI 87,806–134,523), US$88,565 (95% CI 75,678–105,871), US$76,537 (95% CI 67,794–87,917) per QALY gained, respectively. Conclusions: Anti-EGFR therapy is more cost-effective than Bev as a front-line targeted therapy in left-sided pan-RAS WT and pan-RAS WT, with ICER